Application of Jiawei Maxing Shigan Tang in the treatment of COVID-19: An observational study - Wu, Jia; Tang, Feng; Zhang, Xiao-Qiang; Fu, Zai-Lin; Fu, Shui (Frontiers in Medicine, 2022)
Objective: To explore the clinical efficacy and adverse reactions of Jiawei Maxing Shigan Tang (JMST, a modified decoction of ephedra, apricot kernel, gypsum, and licorice) combined with western medicine in the symptomatic treatment of COVID-19. Methods: In this study, we retrospectively collected the basic data of 48 patients with COVID-19 who were discharged from the hospital from January 20 to February 28, 2020. Besides, the blood routines, biochemical indexes, nucleic acid detection results, clinical symptoms, lung imaging improvements, adverse reactions, and other clinical data of these patients before and after treatment were recorded. Finally, we drew comparisons between the outcomes and adverse reactions of patients in the combined treatment group (therapeutic regimen recommended by authoritative guidelines and supplemented by JMST) and the conventional treatment group (therapeutic regimen recommended by authoritative guidelines). Results: There were no significant differences in age, gender, and underlying medical conditions between the combined treatment group (28 cases) and the conventional treatment group (20 cases). However, the combined treatment group presented superior results to the conventional treatment group in several key areas. For instance, patients produced negative nasal/throat swab-based nucleic acid detection results in a shorter time, clinical symptoms were more effectively alleviated, and the absorption time of lung exudation was shorter (P < 0.05). Furthermore, the combined treatment group had a shorter length of stay (LOS) and faster lymphocyte recovery duration than the conventional treatment group, although the difference was not statistically significant. Moreover, there was no significant difference concerning gastrointestinal reaction, hepatic injury, renal impairment, myocardial injury, and other adverse reactions between both groups. Conclusion: The results of this study indicate that JMST combined with the recommended therapeutic regimen enhances the recovery of COVID-19 patients without increasing the risk of adverse reactions. Therefore, this therapy promotes positive outcomes for COVID-19 patients.